Respiratory Tract Problems among Wood Furniture Manufacturing Factory Workers in the Northeast of Thailand - Soongkhang, I.; Laohasiriwong, W. (Kathmandu University Medical Journal, 2017)
Background Wood furniture manufacturing factory workers are at high risk of exposure to wood dust in wood working processes. Wood dust exposure could cause respiratory symptoms, such as reduce lung function, chronic bronchitis, and asthma. The Northeast region of Thailand has many wood furniture manufacturing factories. However, limited studies were carried out to explore the effect of wood dust exposure on workers.Objective This study aimed to assess the respiratory symptoms and determine factors associated with these symptoms among wood furniture manufacturing factory workers.Method This cross-sectional analytical research used a multistage random sampling to select 511 workers from three provinces in the Northeast of Thailand. The data was collected using a structured questionnaire interview. The content validity of questionnaire was tested by 3 experts and had a Cronbach’s alpha coefficient of 0.82. Data were analyzed using descriptive statistics and multiple logistic regressions.Result The result indicated that 29.94% of these workers had respiratory symptoms, including coughing(18.79%), nasal secretion (15.66%), and stuffy nose (15.07%). Factors that were significantly associated with respiratory symptoms (p–value